Reconfiguring Subjectivity in the Hard Problem of Consciousness: Varela’s Neurophenomenology and Mullā Ṣadrā’s Knowledge by Presence - Abdurrahman Abdurrahman; Mohammad Subhi; Dhea Dayuranggi Meghatruh (Jurnal Fuaduna : Jurnal Kajian Keagamaan dan Kemasyarakatan, 2026)
This article examines the problem of subjectivity in David Chalmers’ formulation of the hard problem of consciousness, particularly the difficulty of explaining subjective experience and qualia within a predominantly third-person scientific framework. The study argues that the exclusion or marginalization of the experiencing subject generates both a methodological limitation in investigating consciousness and an epistemic gap in explaining the structure and knowledge of subjective experience. To address this problem, the study comparatively examines Francisco Varela’s neurophenomenology and Mullā Ṣadrā’s metaphysical psychology, bringing them into dialogue with Chalmers’ framework to develop a broader account of subjectivity in consciousness studies. Employing qualitative library research and in-depth analysis of relevant philosophical literature, the study investigates the methodological and epistemological contributions of these two approaches. The findings show that Chalmers’ hard problem reintroduces subjectivity as a fundamental issue in the scientific study of consciousness; Varela’s neurophenomenology provides a methodological framework for incorporating first-person experience through enaction and the embodied interrelation of mind, body, and world; while Ṣadrā’s concept of knowledge by presence (al-ʿilm al-ḥuḍūrī) offers an epistemological account of how subjective experience can be accessed and understood from within. The study concludes that integrating neurophenomenology with Ṣadrā’s epistemology can strengthen both the methodological and epistemological foundations of consciousness studies by connecting first-person inquiry with a deeper account of the structure of subjective experience and qualia.